The role of the synovial fibroblast in rheumatoid arthritis pathogenesis - Turner, Jason D; Filer, Andrew (Current opinion in rheumatology, 2015)
Synovial fibroblasts continue to grow in prominence both as the subjects of research into the pathogenesis of rheumatoid arthritis and as novel therapeutic targets. This timely review aims to integrate the most recent findings with existing paradigms of fibroblast-related mechanisms of disease. Linking the role of synovial fibroblasts as innate sentinels expressing pattern recognition receptors such as toll-like receptors to their effector roles in joint damage and interactions with leukocyte subpopulations has continued to advance. Understanding of the mechanisms underlying increased fibroblast survival in the inflamed synovium has led to therapeutic strategies such as cyclin-dependent kinase inhibition. Major advances have taken place in understanding of the interactions between epigenetic and micro-RNA regulation of transcription in synovial fibroblasts, improving our understanding of the unique pathological phenotype of these cells. Finally, the impact of new markers for fibroblast subpopulations is beginning to become apparent, offering the potential for targeting of pathological cells as the roles of different populations become clearer. Over the past 2 years, major advances have continued to emerge in understanding of the relationship between synovial fibroblasts and the regulation of inflammatory pathways in the rheumatoid arthritis synovium.